2004
DOI: 10.1002/jmor.10237
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugate localization in larval and adult skin of the bullfrog, Rana catesbeiana: A lectin histochemical study

Abstract: This study investigates whether or not the distribution of specific glycoconjugates within the skin is related to the regulation of water balance in the aquatic larvae and semiaquatic adults of the bullfrog, Rana catesbeiana. A lectin histochemical study was carried out on paraffin sections of dorsal and ventral skin from tadpoles in representative stages as well as from adult frogs. Sections were stained with the following horseradish peroxidase (HRP)-conjugated lectins, which bind to specific terminal sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In Rana pipiens, histological features of larval and adult skin are well established (e.g., Bovbjerg, 1963;Fox, 1984Fox, , 1985Mills and Prum, 1984); however, to our knowledge, lectin binding patterns, indicative of cutaneous glycoconjugates, have not been resolved in skin of this species. Yet, numerous studies on lectin binding patterns have been carried out on adult skin of other ranids as well as of aquatic and terrestrial species (review in Kaltenbach et al, 2004). In preliminary research, we found positive lectin staining in larval and adult skin of R. pipiens in all body regions (Kaltenbach et al, 1991;Faszewski and Kaltenbach, 2006); these findings are in contrast to the absence of staining in adult ventral skin of this species as reported by Zaccone et al (1999).…”
mentioning
confidence: 43%
“…In Rana pipiens, histological features of larval and adult skin are well established (e.g., Bovbjerg, 1963;Fox, 1984Fox, , 1985Mills and Prum, 1984); however, to our knowledge, lectin binding patterns, indicative of cutaneous glycoconjugates, have not been resolved in skin of this species. Yet, numerous studies on lectin binding patterns have been carried out on adult skin of other ranids as well as of aquatic and terrestrial species (review in Kaltenbach et al, 2004). In preliminary research, we found positive lectin staining in larval and adult skin of R. pipiens in all body regions (Kaltenbach et al, 1991;Faszewski and Kaltenbach, 2006); these findings are in contrast to the absence of staining in adult ventral skin of this species as reported by Zaccone et al (1999).…”
mentioning
confidence: 43%
“…These results indicate that conical cells express mainly mannose, galactose and partially α(2→3) linked sialic acid bearing glycoconjugates. More recently, it was stated that the secretory cells of the mucous glands express α-fucose and α-galactose in Bufo ictericus (de Brito Gitirana et al 2007) and β-galactose in Rana catesbeiana skin (Kaltenbach et al 2004). These different results may be derived from interspecific diversity.…”
Section: Discussionmentioning
confidence: 99%
“…These different results may be derived from interspecific diversity. On the other hand, there might be a discrepancy in glycoconjugate contents between adult and developing mucous glands; these also could be related to season, habitat and body region from which the skin samples were obtained, as well as the size and gender (Kaltenbach et al 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that glycolipids prevent the access of lysenin to SM (7). Kaltenbach et al (9) examined histochemically changes in glycoconjugates in larval skin at various developmental stages of the bullfrog. The earliest stage they examined was stage V (27), which is equivalent to stage 36 (the stage after the exfoliation period) in Bufo, as judged from the morphological characteristics of the hind-limb bud.…”
Section: Failure To Induce Exfoliation By Cf and Lysenin In Bufo Larvmentioning
confidence: 99%